MEASURING THE EFFECTIVITY OF ACCOUNTING SYSTEM OF CASH IN IN PT. CHITRA MAJU JAYA ABADI JAKARTA - Hamizar (JACTA: Journal of Accounting and Tax, 2022)
The purpose of this study is to find out how the cash receipts accounting system, especially for cash receipts from Cash On Delivery (COD) sales, is applied to PT. Chitra Maju Jaya Abadi.. The research methodology used is in the form of field studies by means of observation and literature study by studying various forms of written materials, as well as interviews with the company. Based on the observations made by the author, it can be concluded that in general PT. Chitra Maju Jaya Abadi has implemented a cash receipts accounting system quite well, it's just that the existing functions are still not in accordance with the existing theory, which results in dual duties and authority by 1 (one) function. The author hopes that the results of research and discussion in this Final Project can provide input that can assist the company in perfecting an effective and efficient Cash Receipt Accounting System.